GMAT Question of the Day - Daily to your Mailbox; hard ones only

 It is currently 16 Oct 2019, 14:59

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# (19 - 18 - 17 - 16) - (20 - 19 - 18 - 17) =

 new topic post reply Question banks Downloads My Bookmarks Reviews Important topics
Author Message
TAGS:

### Hide Tags

Math Expert
Joined: 02 Sep 2009
Posts: 58381
(19 - 18 - 17 - 16) - (20 - 19 - 18 - 17) =  [#permalink]

### Show Tags

05 Jun 2018, 01:31
00:00

Difficulty:

15% (low)

Question Stats:

79% (00:44) correct 21% (00:30) wrong based on 84 sessions

### HideShow timer Statistics

$$(19 - 18 - 17 - 16) - (20 - 19 - 18 - 17) =$$

A. -36

B. -6

C. -4

D. 1

E. 2

_________________
examPAL Representative
Joined: 07 Dec 2017
Posts: 1140
Re: (19 - 18 - 17 - 16) - (20 - 19 - 18 - 17) =  [#permalink]

### Show Tags

05 Jun 2018, 01:52
1
Bunuel wrote:
$$(19 - 18 - 17 - 16) - (20 - 19 - 18 - 17) =$$

A. -36

B. -6

C. -4

D. 1

E. 2

As all we're given are equations, we'll work with them.
This is a Precise approach.

If we're good with mental arithemtic, this is -32 - (-34) = 2

Otherwise, we can simplify:
Since the second parantheses has a minus sign in front of it, when we open it reverses all of the minuses to pluses.
That is, - (20 - 19 - 18 - 17) = -20 + 19 + 18 + 17.
So, our equation can be written as 19 - 18 - 17 - 16 - 20 + 19 + 18 + 17.
Canceling out -18 with + 18 and -17 with + 17 gives 19 - 16 - 20 + 19 = 3 - 1 = 2

(E) is our answer.
_________________
VP
Status: Learning stage
Joined: 01 Oct 2017
Posts: 1017
WE: Supply Chain Management (Energy and Utilities)
Re: (19 - 18 - 17 - 16) - (20 - 19 - 18 - 17) =  [#permalink]

### Show Tags

05 Jun 2018, 01:53
1
Bunuel wrote:
$$(19 - 18 - 17 - 16) - (20 - 19 - 18 - 17) =$$

A. -36

B. -6

C. -4

D. 1

E. 2

$$(19 - 18 - 17 - 16) - (20 - 19 - 18 - 17)$$
=$$(1-17-16)-(1-18-17)$$
=$$(-16-16)-(-17-17)$$
=-32-(-34)
=-32+34
=2

Ans. option E.
_________________
Regards,

PKN

Rise above the storm, you will find the sunshine
VP
Joined: 31 Oct 2013
Posts: 1469
Concentration: Accounting, Finance
GPA: 3.68
WE: Analyst (Accounting)
Re: (19 - 18 - 17 - 16) - (20 - 19 - 18 - 17) =  [#permalink]

### Show Tags

05 Jun 2018, 02:41
1
Bunuel wrote:
$$(19 - 18 - 17 - 16) - (20 - 19 - 18 - 17) =$$

A. -36

B. -6

C. -4

D. 1

E. 2

To solve this this just uncover the bracket multiplying by -1.

19-18-17-16-20+19+18+17
=(19*2)-36
=38-36
=2
Thus option E is the correct answer.
Intern
Joined: 17 Apr 2013
Posts: 34
Re: (19 - 18 - 17 - 16) - (20 - 19 - 18 - 17) =  [#permalink]

### Show Tags

19 Oct 2018, 11:16
(19−18−17−16)−(20−19−18−17)
=19-20-18+19-17+18-16+17
=-1+1+1+1
=2

Give me a kudo if this helped
Re: (19 - 18 - 17 - 16) - (20 - 19 - 18 - 17) =   [#permalink] 19 Oct 2018, 11:16
Display posts from previous: Sort by

# (19 - 18 - 17 - 16) - (20 - 19 - 18 - 17) =

 new topic post reply Question banks Downloads My Bookmarks Reviews Important topics

 Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne